Many-body physics of single and double spin-flip excitations in NiO - Nag, Abhishek; Robarts, H. C.; Wenzel, Fabian; Li, J.; Elnaggar, Hebatalla; Wang, Ru-Pan; Walters, A. C.; García-Fernández, M.; Groot, F. M. F. de; Haverkort, Maurits W.; Zhou, Ke-Jin (Physical review letters, 2020)
Understanding many-body physics of elementary excitations has advanced our control over material properties. Here, we study spin-flip excitations in NiO using Ni L3-edge resonant inelastic x-ray scattering (RIXS) and present a strikingly different resonant energy behavior between single and double spin-flip excitations. Comparing our results with single-site full-multiplet ligand field theory calculations we find that the spectral weight of the double-magnon excitations originates primarily from the double spin-flip transition of the quadrupolar RIXS process within a single magnetic site. Quadrupolar spin-flip processes are among the least studied excitations, despite being important for multiferroic or spin-nematic materials due to their difficult detection. We identify intermediate state multiplets and intra-atomic core-valence exchange interactions as the key many-body factors determining the fate of such excitations. RIXS resonant energy dependence can act as a convincing proof of existence of nondipolar higher-ranked magnetic orders in systems for which, only theoretical predictions are available.